Further delineation of GEMIN4 related neurodevelopmental disorder with microcephaly, cataract, and renal abnormalities syndrome. Issue 10 (21st July 2022) - Altassan, Ruqaiah; Qudair, Ahmad; Alokaili, Riyadh; Alhasan, Khalid; Faqeih, Eissa A.; Alhashem, Amal; Alowain, Muhammed; Alsayed, Moeanaldeen; Rahbeeni, Zuhair; Albadi, Lama; Alkuraya, Fowzan S.; Anderson, Eric N.; et al.
Abstract: Pathogenic variants in GEMIN4 have recently been linked to an inherited autosomal recessive neurodevelopmental disorder characterized with microcephaly, cataracts, and renal abnormalities (NEDMCR syndrome). This report provides a retrospective review of 16 patients from 11 unrelated Saudi consanguineous families with GEMIN4 mutations. The cohort comprises 11 new and unpublished clinical details from five previously described patients. Only two missense, homozygous, pathogenic variants were found in all affected patients, suggesting a founder effect. All patients shared global developmental delay with variable ophthalmological, renal, and skeletal manifestations. In addition, we knocked down endogenous Drosophila GEMIN4 in neurons to further investigate the mechanism of the functional defects in affected patients. Our fly model findings demonstrated developmental defects and motor dysfunction suggesting that loss of GEMIN4 function is detrimental in vivo; likely similar to human patients. To date, this study presents the largest cohort of patients affected with GEMIN4 mutations. Considering that identifying GEMIN4 defects in patients presenting with neurodevelopmental delay and congenital cataract will help in early diagnosis, appropriate management and prevention plans that can be made for affected families.